Pengetahuan Ibu Tentang Makanan Pendamping ASI (MP-ASI) Dengan Status Gizi Balita Usia 6-24 Bulan Di Puskesmas Mojosari Kabupaten Mojokerto - Dyah siwi hety hety (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
This research is conducted to identify knowledge of mother about MP ASI in child age 6-24 months. This research represent analytic research with approach of crossectional, population taken away from by all respondents having age baby 6-24 months in Health Center Mojosari districts Mojokerto. Samples used 17 respondents, technique from other side the used is sampling probability, and sampling by using test of rank spearman. Result of research indicate that mother majority have knowledge enough that is 42 respondents ( 60%) which bad status are 27 respondents ( 38,6%), evaluated from respondents age can know that most respondents have age to 20-30 year, evaluated from education of mother most education of SMP while evaluated from work faced most mother work. To get clarification having a meaning of researcher use test of spearman with result of t calculate 6.0 > t of tables of its 1.98 meaning there is relation which is dignifikan between knowledge of mother about MP-ASI with status of gizi age balita 6-24 months. Knowledge represent important domain which determine to be formed his of behavior, good knowledge will push someone to give MP-ASI at its baby better. Conclusion of this research that knowledge of mother about MP-ASI enough, with status of gizi its of ugly him. Hence expected by nakes give counselling, guidance, and demonstration about MP-ASI to mothers so that mothers more comprehending and understanding about is important of him of MP-ASI to baby and his child.